Mycoplasma synoviae lipid-associated membrane proteins identification and expression changes when exposed to chicken cells - Si, Duoduo; Sun, Jialin; Guo, Lei; Yang, Fei; Li, Jidong; He, Shenghu (Frontiers in Veterinary Science, 2023)
Mycoplasma synoviae (M. synoviae) is a significant cause of respiratory disease and synovitis among chickens, and has an adverse economic impact on broiler breeding efforts. The present study was designed to develop a systematic understanding of the role that M. synoviae lipid-associated membrane proteins (LAMPs) may play in the virulence of this pathogen. Bioinformatics tools were used to identify 146 predicted membrane proteins and lipoproteins in the M. synoviae proteome. Then, Triton X-114 was used to extract LAMPs that were subsequently identified via LC-MS/MS. This approach enabled the detection of potential LAMPs, and the top 200 most abundant proteins detected using this strategy were subject to further analyses. M. synoviae cells (100 MOI) were exposed to chicken fibroblasts (DF-1) and macrophages (HD-11) in a 1:1 mixed culture. Analysis of LAMP transcripts identified 72 up-regulated LAMP genes which were analyzed in depth by bioinformatics. GO analyses revealed these genes to be enriched in the nucleotide binding, sulfur amino acid transmembrane transporter activity, tRNA binding, rRNA modification, and transition metal ion transport pathways.Moreover, KEGG enrichment analyses suggested that these genes were enriched in the biosynthesis of secondary metabolites, carbon metabolism, glycolysis/gluconeogenesis, and nitrogen metabolism pathways.